Tranexamic Acid Treatment for Trauma Victims - Roberts, Ian; Brenner, Amy; Shakur-Still, Haleema (Seminars in Thrombosis and Hemostasis, 2021)
Worldwide, traumatic injury is responsible for over 5 million deaths per year, the majority due to exsanguination and head injury. The antifibrinolytic drug tranexamic acid is the only drug proven to reduce deaths after traumatic injury. Several large randomized controlled trials have provided high-quality evidence of its effectiveness and safety in trauma patients. Early tranexamic acid reduces deaths on the day of the injury in polytrauma patients and patients with isolated traumatic brain injury by around 20%. Treatment is time critical; for patients to benefit, tranexamic acid must be given as soon as possible after injury. Intramuscular administration is well tolerated and rapidly absorbed, with the potential to reduce time to treatment. Because the proportional reduction in bleeding death with tranexamic acid does not vary by baseline risk, a wide range of trauma patients stands to benefit. There are far more low-risk trauma patients than high-risk patients, with a substantial proportion of bleeding deaths in the low-risk group. As such, treatment should not be limited to patients with severe traumatic hemorrhage. We must give paramedics and physicians the confidence to treat a far wider range of trauma patients while emphasizing the importance of early treatment.
Keywords: hemorrhage; trauma; traumatic brain injury; tranexamic acid; fibrinolysis